HUBUNGAN POLA ASUH ORANG TUA TERHADAP KENAKALAN REMAJA DI DUKUH KERSAN DESA JATISOBO TAHUN 2020 - Saka Suminar; Rara Intan Mutiara F (Jurnal Kesehatan Tujuh Belas (Jurkes TB), 2020)
ABSTRAK Pola asuh adalah upaya memelihara, merawat, membimbing, membina dan mendidik anak-anaknya baik masih kecil hingga dewasa. Faktor yang mempengaruhi pola asuh pada orang tua dipengaruhi oleh pendidikan orang tua, lingkungan, suku, status perkawinan, pekerjaan, jumlah anak. Pola asuh yang salah dapat membentuk karakter diri yang negatif sehingga remaja cenderung akan melakukan Kenakalan remaja seperti seks bebas, minum-minuman keras, merokok. Penelitian ini bertujuan untuk mengetahui hubungan pola asuh orang tua dengan perilaku kenakalan remaja di dukuh Kersan desa Jatisobo. Jenis dan rancangan dalam penelitian ini adalah deskriptif dengan jumlah populasi 10 responden. Tehnik pengambilan sample dengan metode total sampling, pengumpulan data menggunakan kuesioner. Analisa dalam penelitian ini menggunakan analisa univariate dan bivariate. Hasil uji Spearman Rank menunjukkan nilai p sebesar 0,000 a ? 0,05, sehingga dinyatakan bahwa ada hubungan pola asuh orang tua dengan perilaku kenakalan remaja. Pola asuh orang tua yang salah dapat mengakibatkan dampak buruk tejadinya kenakalan remaja sehingga peran orang tua dalam membentuk kepribadian remaja sangat mempengaruhinya. Kata kunci : pola asuh orang tua, kenakalan remaja RELATIONSHIP BETWEEN PARENTS AND JUVENILE DELINQUENCY AT KERSAN JATISOBO VILLAGE IN 2020 ABSTRACT Parenting is the effort to nurture, care, guide, nurture and educate their children both as a child to adulthood. Factors affecting parenting patterns in the elderly are influenced by parent, ward, tribal, marital, occupational, number of children. Wrong pattern of foster can form a negative self-character so that teenagers tend to do juvenile delinquency such as free sex, drinking, smoking. Foster parenting is the effort to nurture, care, guide, nurture and educate their children both as a child to adulthood. Factors affecting parenting patterns in the elderly are influenced by parent, ward, tribal, marital, occupational, number of children. Wrong pattern of foster can form a negative self-character so that teenagers tend to do juvenile delinquency such as free sex, drinking, smoking. This study aims to determine the relationship of parenting parents with behavior of juvenile delinquency in Hamlet Kersan Jatisobo village. Type and design in this research is descriptive with population of 10 respondents. Sampling technique with total sampling method, data collection using questionnaire. Analysis in this research using univariate and bivariate analysis. Spearman Rank test results show p value of 0,000 a ? 0.05, so it is stated that there is a relationship parenting parents with behavior of juvenile delinquency. Parenting false parents who can cause a bad impact of juvenile delinquency so that the role of parents in shaping the personality of adolescents greatly affect it. Parental parenting, juvenile delinquencySpearman Rank test results show p value of 0,000 a ? 0.05, so it is stated that there is a relationship parenting parents with behavior of juvenile delinquency. Parenting false parents who can cause a bad impact of juvenile delinquency so that the role of parents in shaping the personality of adolescents greatly affect it. Keywords: parenting, juvenile delinquency